Tata Kelola, Pengendalian Internal, dan Kinerja Keuangan Perusahaan Manufaktur di Indonesia - Vonny Faustina Koeswanto; Agnes Utari Widyaningdyah (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
Good corporate governance can support companies in improving their performance, especially in their financial performance, by assisting in decision making, so it can be said that governance is important for companies. The implementation of good corporate governance can also increase the value of the company and increase investor confidence. Good corporate governance cannot be implemented without good internal control, where internal control supports the implementation of governance so that financial performance can be better. Internal control helps in monitoring so that corporate governance can run well in order to achieve company goals.We investigate the influence of governance on the financial performance of manufacturing companies with the support of internal control. The study was conducted using the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. Moderated Regression Analysis (MRA) was using in this study. The results indicate that corporate governance is able to improve the company's financial performance, but has not been able to prove the moderator role of internal control on the influence of corporate governance on the financial performance.